Rifampicin-resistant Mycobacterium tuberculosis: susceptibility to isoniazid and other anti-tuberculosis drugs - Kurbatova, Ekaterina V. (Int J Tuberc Lung Dis, 2012)
Based on data from 14 Supranational Tuberculosis (TB) Reference Laboratories worldwide, the proportion of rifampicin-resistant isolates that were isoniazid-susceptible by phenotypic drug-susceptibility tests varied widely (0.5%–11.6%). Rifampicin-resistant isolates that were isoniazid-susceptible had significantly lower rates of resistance to other first-line and second-line anti-TB drugs (except rifabutin) compared to multidrug-resistant isolates. Rifampicin resistance is not always a good proxy for a presumptive diagnosis of multidrug-resistant tuberculosis, which has implications for use of molecular assays that identify only rifampicin resistance-associated DNA mutations.